The Effect of Pass and Move Training on The Passing Skills of Extracurricular Futsal Students of SMPN 13 Bandar Lampung - Saputra, Kurnia Gilang; Mahfud, Imam (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Futsal has now become a favorite sport for people all over the world from children to adults. The purpose of this study was to determine the effect of pass and move training on the passing skills of extracurricular futsal students at SMPN 13 Bandar Lampung. This type of research is descriptive quantitative with an experimental method. The data collection instrument in this study used a passing controlling test. The population of this study was 20 students who took extracurricular activities at SMPN 13 Bandar Lampung, so that the entire population was used as a research sample with a total sampling technique totaling 20 extracurricular students at SMPN 13 Bandar Lampung. The data analysis technique in this study was supported by SPSS 25 software through the analysis that will be used as follows. (1) Data normality test> 0.05 normally distributed, (2) Homogeneity test using the Levene-test> 0.05 homogeneous data, (3) Research hypothesis using the t-test (paired sampled t-test) with a sig. level <0.05. The results of the study showed that there was an effect of pass and move training on the passing skills of extracurricular futsal students at SMPN 13 Bandar Lampung with a sig value of 0.000 <0.05. Thus, the pass and move training method can be used as a reference for futsal passing training programs in practice in improving futsal passing performance so that players can make decisions correctly and quickly in terms of the direction of passing the ball.